2021
DOI: 10.1371/journal.pone.0253464
|View full text |Cite|
|
Sign up to set email alerts
|

Dynamic linkages between renewable energy, carbon emissions and economic growth through nonlinear ARDL approach: Evidence from Iran

Abstract: This study examines the relationship between economic growth, renewable energy consumption, and carbon emissions in Iran between 1975–2017, and the bounds testing approach to cointegration and the asymmetric method was used in this study. The results reveal that in the long run increase in renewable energy consumption and CO2 emissions causes an increase in real GDP per capita. Meanwhile, the decrease in renewable energy has the same effect, but GDP per capita reacts more strongly to the rise in renewable ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Previous studies on the relationship between RE consumption, emissions, and economic growth indicate that these relationships depend on the level of economic development of a country, and repeatedly confirm the existence of bidirectional relationships between these phenomena [41][42][43][44][45], especially in the long term [46]. Yang et al found evidence that investment in RE projects leads to significant economic growth and reduces emissions risks [47].…”
Section: Importance Of Re Developmentmentioning
confidence: 88%
“…Previous studies on the relationship between RE consumption, emissions, and economic growth indicate that these relationships depend on the level of economic development of a country, and repeatedly confirm the existence of bidirectional relationships between these phenomena [41][42][43][44][45], especially in the long term [46]. Yang et al found evidence that investment in RE projects leads to significant economic growth and reduces emissions risks [47].…”
Section: Importance Of Re Developmentmentioning
confidence: 88%
“…More so, Kamiri et al, [39] employed bound tests and asymmetric methodologies in establishing empirical perspectives on REC, CO 2 emissions and GDP, using Iran as a case study. The crux of their study was that in the long run, increased economic growth per capita will ultimately be propelled by REC and GHG emissions.…”
Section: Renewable Energy As An Engine Of Economicmentioning
confidence: 99%
“…Likewise, Karimi et al (2021) investigated the relationship between economic growth, renewable energy consumption, and carbon emissions in Iran during 1975-2017. The authors followed the testing of the limits technique to cointegration and the asymmetric methods in the paper.…”
Section: Literature Reviewmentioning
confidence: 99%